2017
DOI: 10.1038/ncomms14556
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in microglial CX3CR1 signalling determine obesity susceptibility in mice

Abstract: Female mice are less susceptible to the negative metabolic consequences of high-fat diet feeding than male mice, for reasons that are incompletely understood. Here we identify sex-specific differences in hypothalamic microglial activation via the CX3CL1-CX3CR1 pathway that mediate the resistance of female mice to diet-induced obesity. Female mice fed a high-fat diet maintain CX3CL1-CX3CR1 levels while male mice show reductions in both ligand and receptor expression. Female Cx3cr1 knockout mice develop ‘male-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 70 publications
(107 reference statements)
11
140
0
Order By: Relevance
“…Interestingly, it has been recently reported that there are sex‐specific differences in hypothalamic microglial activation via the CX3CL1‐CX3CR1 pathway and that such differences are not mediated by estrogen (Dorfman et al . ). Here, we find concomitant injury to POMC neurons and microglia activation in the arcuate nucleus of male mice, but not female mice, exposed to HF diet.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, it has been recently reported that there are sex‐specific differences in hypothalamic microglial activation via the CX3CL1‐CX3CR1 pathway and that such differences are not mediated by estrogen (Dorfman et al . ). Here, we find concomitant injury to POMC neurons and microglia activation in the arcuate nucleus of male mice, but not female mice, exposed to HF diet.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, HFD resulted in diminished CX3CL1/CX3CR1 signaling specifically in microglia of male mice, which corresponded with increased hypothalamic inflammation and glucose intolerance in these mice. Knockout of CX3CR1 in females resulted in a similar male‐like phenotype (Dorfman et al, ). The female‐specific protections were not altered by acute estradiol injection, suggesting intrinsic differences in hypothalamic male and female microglia in response to HFD that impact whole body glucose homeostasis.…”
Section: Intrinsic Immunometabolic Programming May Impart Sex Differementioning
confidence: 91%
“…HFD in males diminished CX3CR1 signaling and led to an enhanced inflammatory response, while in females CXCL1 protein was increased, but overall CXC3R1 signaling remained relatively unaffected, and no increased inflammation was observed. This figure is based on data presented in Orihuela, McPherson, and Harry (), Jaber et al (), Voloboueva, Emery, Sun, and Giffard (), L. Wang et al (), Dorfman et al ()…”
Section: Intrinsic Immunometabolic Programming May Impart Sex Differementioning
confidence: 98%
“…Sex differences in microglial activation have been implicated in the modulation of energy homeostasis. This was shown in the hypothalamic microglial activated CX3CL1‐CXCLR1 pathway in a mouse model of obesity . Dorfman et al found that increased CXCLR1, which is associated with energy expenditure, allowed for females to be more resistant to obesity .…”
Section: Microglial Sex Differences In Homeostatic Adult Brainmentioning
confidence: 90%